Javardise: a projectional code editor for Java - André L. Santos (Strumenta Virtual Meetup, 2022)
Structured editors have for long been envisioned as a promising approach to write code, as by design their interaction techniques are capable of preventing syntax errors to a great extent. However, this sort of editors have never gained wide adoption since their inception back in the 80’s. Apart from Jetbrain’s MPS (Meta Programming System), there are barely any industry-strength tools that promote the use of structured editors. Regarding academic research, the activity in the topic is somewhat scarce. This talk is about on-going work on Javardise, a research prototype of a structured editor for Java. At this point, the work is focused on facilitating the learning process of novice programmers, but nevertheless, we envision a meaningful purpose for non-beginners. The tool is implemented as a projectional editor built on top of the model provided by JavaParser — a library for reengineering Java code with high-level abstractions — and Eclipse’s SWT as the GUI toolkit. In addition to structured code editing views, our aim is to break the tyranny of source file-oriented views, and explore new ways of organising, viewing, and editing the code, leveraging on projectional editing.